KOMPETENSI KOMUNIKASI DAN SOSIO-EMOSIONAL GURU DALAM MEWUJUDKAN PEMBELAJARAN BERMAKNA DI PRATAMA WIDYALAYA SERATHI DHARMA KABUPATEN LUWU TIMUR - Kartika, Komang Reza; Astraguna, I Wayan; Febriyani, Ida Ayu Indah; Larasaty, Inten (Fakultas Dharma Acarya IAHN-TP Palangka Raya, 2026)
Meaningful learning positions students as individuals who develop holistically in the cognitive, affective, social, and spiritual domains. In this context, teachers' communication and socio-emotional competencies are key factors in building quality learning experiences. A number of studies show that these two competencies contribute significantly to the quality of learning, but are generally still studied separately. This study aims to comprehensively examine the integration of teachers' communication and socio-emotional competencies in realising meaningful learning in holistic learning at Pratama Widyalaya Serathi Dharma, East Luwu Regency. This study uses a descriptive qualitative approach with observation, interview, and documentation techniques. Informants were selected purposively based on their relevance and competence to the research object. Data analysis used the Miles and Huberman model, namely data reduction, data presentation, and conclusion drawing. The findings show that teachers' communication competencies, including discourse, linguistic, actional, sociocultural, and strategic competencies, contribute to creating effective and contextual learning interactions. Meanwhile, teachers' socio-emotional competencies, which include self-awareness, self-control, motivation, empathy, and social skills, contribute to building a humanistic, safe, and inclusive classroom climate. The integration of these two competencies forms a synergy that supports the realisation of meaningful learning oriented towards academic achievement, character development, social skills, and spiritual awareness of students in accordance with Hindu educational values. Therefore, this study recommends strengthening teacher competencies through various planned and continuous professional development programmes for teachers to improve the quality and sustainability of learning.